Theoretical Investigation on Microcavity Coupler for Terahertz Quantum-Well Infrared Photodetectors - Xuguang Guo; Yuxiang Ren; Guixue Zhang; Anqi Yu; Xiaoshuang Chen; Yiming Zhu (IEEE Access, 2020)
Resonant behaviors and absorption enhancement of metallic grating-dielectric-metal (GDM) microcavity are theoretically investigated. The GDM structure is treated as periodic unit cells of two serially-connected metal-dielectric-metal (MDM) and air-dielectric-metal (ADM) waveguide resonators. The resonant modes can be divided into three types: the LC mode, the TEM modes supported by the MDM waveguide resonator, and the TEM-TM hybrid modes supported by the whole GDM structure. The resonant frequencies of LC and TEM modes are independent on a small incident oblique angle. However, for the TEM-TM hybrid modes, each mode splits into two branches with non-zero incident angles. Based on the temporal coupled-mode theory, the intersubband absorption efficiency of multi quantum wells inserted into the GDM microcavity is calculated and discussed qualitatively. We point out that the condition of critical coupling is not the optimal condition for intersubband absorption efficiency when the metallic loss cannot be neglected. An optimization procedure is given for the design of high performance GDM-microcavity-coupled terahertz quantum-well infrared photodetectors.